2018
DOI: 10.1016/j.diabres.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Are glucose profiles well-controlled within the targets recommended by the International diabetes Federation in type 2 diabetes? A meta-analysis of results from continuous glucose monitoring based studies

Abstract: glucose profiles well-controlled within the targets recommended by the International Diabetes Federation in type 2 diabetes? A meta-analysis of results from continuous glucose monitoring based studies',

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
2
0
1
Order By: Relevance
“…However, high post-breakfast is consistently observed in type 2 diabetes. 19,20 It is more common than high post-lunch glucose and post-dinner glucose because the circadian glycaemic profile tends to be the highest after breakfast. 19,20 The present study suggests that interrupting sedentary time every 15 min with light-intensity walking breaks should be recommended to improve post-meal glucose, particularly for post-breakfast glucose, in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…However, high post-breakfast is consistently observed in type 2 diabetes. 19,20 It is more common than high post-lunch glucose and post-dinner glucose because the circadian glycaemic profile tends to be the highest after breakfast. 19,20 The present study suggests that interrupting sedentary time every 15 min with light-intensity walking breaks should be recommended to improve post-meal glucose, particularly for post-breakfast glucose, in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of glucose control before and after meals, and every 1 mmol/L increase in pre-meal glucose and post-meal glucose can increase the risk of a cardiovascular event by 11% and 8%, respectively (Kilpatrick et al 2008). However, it has been shown that glucose control before and after meals, particularly pre-breakfast glucose and post-breakfast glucose, are suboptimal in people with type 2 diabetes, even in those taking anti-diabetes agents (van Dijk et al 2011;Paing et al 2018a). Therefore, high incidence of diabetesrelated complications tends to occur in people with type 2 diabetes (Nazimek-Siewniak et al 2002;Cavalot et al 2011;Jelinek et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Los autores calificaron la mayoría de los estudios como con alto riesgo de sesgo. Otra RS publicada por Paing et al en 2018 128 incluyó 12 estudios observacionales (731 participantes). La precisión diagnóstica de los distintos dispositivos de MCG se llevó a cabo mediante el cálculo de las diferencias de las medias relativas absolutas, los cuales mostraron un rango del 9.9 al 20.6% 128 .…”
Section: Revisión De La Literatura Y Análisisunclassified
“…Otra RS publicada por Paing et al en 2018 128 incluyó 12 estudios observacionales (731 participantes). La precisión diagnóstica de los distintos dispositivos de MCG se llevó a cabo mediante el cálculo de las diferencias de las medias relativas absolutas, los cuales mostraron un rango del 9.9 al 20.6% 128 . Las conclusiones de los autores es que los dispositivos permiten una medición precisa del perfil de glucemia durante el día, encontrando una discrepancia entre el nivel de control glucémico que no se ve reflejada en los valores de HbA1c, ya que pacientes con menos de 10 años de evolución y cifras de HbA1c < 7.0% mostraron variaciones diarias importantes 128 .…”
Section: Revisión De La Literatura Y Análisisunclassified